2017
DOI: 10.1590/1982-0224-20160094
|View full text |Cite
|
Sign up to set email alerts
|

Colorful invasion in permissive Neotropical ecosystems: establishment of ornamental non-native poeciliids of the genera Poecilia/Xiphophorus (Cyprinodontiformes: Poeciliidae) and management alternatives

Abstract: Headwater creeks are environments susceptible to invasion by non-native fishes. We evaluated the reproduction of 22 populations of the non-native livebearers guppy Poecilia reticulata, black molly Poecilia sphenops, Yucatan molly Poecilia velifera, green swordtail Xiphophorus hellerii, southern platyfish Xiphophorus maculatus, and variable platyfish Xiphophorus variatus during an annual cycle in five headwater creeks located in the largest South American ornamental aquaculture center, Paraíba do Sul River basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 37 publications
0
36
0
6
Order By: Relevance
“…Recent evaluations revealed that we should be concerned with the introduction of a “few widespread” species (Toussaint, Beauchard, et al., ), either unintentionally, because it culminates in biological invasions and biotic homogenization (Mazor et al., ; Pool & Olden, ; Toussaint, Charpin, et al., ). An outstanding example is the widespread occurrence of non‐native cichlid (Lima Junior et al., 2018) and cyprinid (Magalhães & Jacobi, ; Rodrigues‐Filho et al., ) fish in natural and artificial environments of South America and worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evaluations revealed that we should be concerned with the introduction of a “few widespread” species (Toussaint, Beauchard, et al., ), either unintentionally, because it culminates in biological invasions and biotic homogenization (Mazor et al., ; Pool & Olden, ; Toussaint, Charpin, et al., ). An outstanding example is the widespread occurrence of non‐native cichlid (Lima Junior et al., 2018) and cyprinid (Magalhães & Jacobi, ; Rodrigues‐Filho et al., ) fish in natural and artificial environments of South America and worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Aquarium trade, baiting, fish farming, sports fishing and stocking policies are the main activities resulting in the introduction of companion species, non‐native species that are introduced jointly with another non‐native species of economic relevance (Magalhães and Jacobi, ; Abilhoa, Bornatowski, & Vitule, ; Daga et al., ). Evolutionary novelties among newly introduced non‐natives, such as rapid growth and resistance to diseases, may confer advantages over the native biota (Padilla & Williams, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this order, the family Poeciliidae comprises 42 genera with about 353 species (Nelson, Grande, & Wilson, ), which are small and laterally compressed fishes, with body form ranging from extremely elongated (e.g., Tomeurus ) to deep‐bodied (e.g., Phallichthys , Carlhubbsia ) (Lucinda, ). Some species have been introduced in many countries by ornamental aquarists (Magalhães & Jacobi, ), and as an alternative measure to biological control of mosquitoes (Azevedo‐Santos, Vitule, Pelicice, & García‐berthou, ). Seven species were already registered in Brazilian headwater streams (Magalhães & Jacobi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Revista de Biología Tropical,68(1),[122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138] caso de ciertas especies del género Poecilia, son la ovovivíparidad (Courtenay & Meffe, 1989), el cuidado parental (Magurran, Seghers, Carvalho, & Shaw, 1992) y la formación de cardúmenes (Camacho-Cervantes, García, Ojanguren, & Magurran, 2014a; Camacho-Cervantes, Ojanguren, Deacon, Ramnarine, & Magurran, 2014b); además, por ejemplo, las hembras de P. reticulata tiene la capacidad de almacenar esperma hasta por 10 meses (López-Sepulcre, Gordon, Paterson, Bentzen, & Reznick, 2013), lo que le permite a una hembra, por si misma, colonizar una nueva localidad, y fundar una población estable (Deacon, Ramnarine, & Magurran, 2011;Deacon & Magurran, 2016). Algunos autores (Meyer, Salzburger, & Schartl, 2006;Lampert & Schartl, 2008) reportan la hibridización entre especies emparentadas de Poecilia, lo que a su vez podría incrementar el riesgo de extinción para las especies locales (Magalhães & Jacobi, 2017). Se ha demostrado que los poeciliidos han sido la causa de la disminución en las poblaciones de algunos cyprínidos endémicos de Norteamérica (Magurran, 2009).…”
unclassified